2016
DOI: 10.3109/09286586.2015.1130845
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid, Vitamin B6, and Vitamin B12in Combination and Age-Related Cataract in a Randomized Trial of Women

Abstract: Purpose To examine incidence of cataract and cataract extraction in a trial of folic acid and vitamins B6 and B12. Methods In a randomized, double-masked, placebo-controlled trial, 5,442 female health professionals aged 40 years or older with preexisting cardiovascular disease (CVD) or 3 or more CVD risk factors were randomly assigned to receive a combination of folic acid (2.5mg/day), vitamin B6 (50mg/day), and vitamin B12 (1mg/day), or placebo. A total of 3,925 of these women did not have a diagnosis of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Furthermore, in large, prospective, population-based cohorts it was found that high-dose Vitamin C or Vitamin E supplements had a statistically significant increased risk of age-related cataract [15], most likely due to the pro-oxidative properties of Vitamins C and E at high doses reported in in vitro studies [16,17]. While in a large-scale randomized trial of women at high risk of cardiovascular disease, daily supplementation with a combination of folic acid, vitamin B 6 , and vitamin B 12 had no significant effect on cataract, but may have increased the risk of cataract extraction [18]. However, high intake of dietary vitamin K 1 was associated with a reduced risk of cataracts in an elderly Mediterranean population even after adjusting by other potential confounders [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in large, prospective, population-based cohorts it was found that high-dose Vitamin C or Vitamin E supplements had a statistically significant increased risk of age-related cataract [15], most likely due to the pro-oxidative properties of Vitamins C and E at high doses reported in in vitro studies [16,17]. While in a large-scale randomized trial of women at high risk of cardiovascular disease, daily supplementation with a combination of folic acid, vitamin B 6 , and vitamin B 12 had no significant effect on cataract, but may have increased the risk of cataract extraction [18]. However, high intake of dietary vitamin K 1 was associated with a reduced risk of cataracts in an elderly Mediterranean population even after adjusting by other potential confounders [19].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 4 ] Cataract is a common cause of visual impairment in the elderly population; reduced antioxidant and oxidative stress are associated with the pathogenesis of senile cataract. [ 5 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…To date, 6 epigenetic drugs have been approved by the FDA for cancer therapy [ 51 ]. A variety of epigenetic drugs, including DNMT and HDAC inhibitors are currently under investigation as potential therapeutic agents in AMD, owing to their ability to reverse inflammation and angiogenesis [ 55 , 86 ]. Specific HDAC inhibitors might be preferable to pan-inhibitors, such as TSA, as the latter can cause undesirable alterations in gene expression by inducing histone hyperacetylation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%